Deliberate sulphonylurea poisoning mimicking hyperinsulinaemia of infancy. Issue 5 (1st May 2000) - Owen, Louise; Ellis, Matthew; Shield, Julian
Abstract : A 6 month old child presenting with seizures was found to be hypoglycaemic secondary to hyperinsulinism. A family history of type II diabetes prompted estimation of sulphonylurea in the baby's blood, which was found to be high. A multidisciplinary case conference concluded that the sulphonylurea ingestion was likely to be the result of Munchausen syndrome by proxy. When investigating hypoglycaemia of infancy this possibility should be considered.